Duelo de imagens e palavras: o "acordo" do Cinturão Verde de Cianorte e a cobertura dos jornais impressos locais e estaduais - Lima, Aida Franco de (2010)
This work focuses on analysis of an episode which took place in the Northwestern region of Paraná more specifically in the city of Cianorte and called media s attention from 1998 to 2001. The event, named here as "The Agreement on Cianorte's Green Belt" put under the lights a 542,13-hectare green area owned by a private company which turned into a bargaining chip between the company and Parana`s state in order to ensure the preservation of a part to the detriment deforestation and the consequent subdivision of another. This report s overall objective meets the analysis of The Agreement s press coverage, emphasizing two local newspapers. When it comes to this report s specific objectives, they focus on the purpose of briefly describing the colonization process of Cianorte s area as well as perceiving the role of environmental journalism and media image as legitimizing agents on Green Belt s devastation. At the same time, this research aimed to identify the social actors involved, their interests and Green Belt s matter developments through papers. It is possible to perceive an imagery and discursive duel between two oppositional local newspapers while the episode occurred. Therefore, each press media molded texts and images according to their editorial, economical and political interests, sometimes taking some evidences for granted. Thus, popular involvement and the subject s emphasis given by external vehicles provided a new case s outcome. The analysis of the event s background based on flashy news content collected in about two years when the case was still being broadcasted by media constitutes the corpus of this research. Its theoretical support lies on the concepts of "Iconofagy (Baitello); Garden City (Howard), GM and Hollywood Journalism (Marshall and Novaes, respectively); Cultural Miscegenation (Pinheiro) and some other important contributions from different authors